Collective risk model - Škerlep, Domen Gal (Matrika, 2021)
One of the main tasks of actuaries is to make the best possible predictions for the sum of insurance claim amounts in a specific time interval. There are several possible approaches that all to a certain extent give accurate values. One of them is the collective risk model, which is defined in this article. Using Wald's Identity and linear regression the expected sum of insurance claims for helicopter rescuing in one year is calculated.
Keywords: actuarial science; aktuarstvo; distributions; insurance; porazdelitve; probability; verjetnost; zavarovalništvo